Race, media, and the crisis of civil society : from Watts to Rodney King - Jacobs, Ronald N. (Cambridge ; New York : Cambridge University Press, 2000)
Comparing African-American and mainstream US newspaper coverage of some of the most important racial crises of the post-war period, this text argues that a strong African-American press is still needed today.
Race, media, and multiple publics -- Historicizing the public spheres: New York, Los Angeles, Chicago -- Watts uprisings of 1965 -- Rodney King beating -- Rodney King 1992.
Includes bibliographical references (pages 175-185) and index.
Print version record.
eBooks on EBSCOhost
Keywords: African Americans and mass media; Mass media and race relations -- United States; African Americans in mass media; African American press; Mass media -- Social aspects -- United States; United States -- Race relations; Noirs américains et médias.; Médias et relations raciales -- États-Unis.; Noirs américains dans les médias.; Presse noire américaine.; Médias -- Aspect social -- États-Unis.; États-Unis -- Relations raciales; SOCIAL SCIENCE -- Media Studies; African American press; African Americans and mass media; African Americans in mass media; Mass media and race relations; Mass media -- Social aspects; Race relations; United States; Rassenunruhen; Massenmedien; Ethnische Beziehungen; USA; Schwärze; Massamedia; Berichtgeving; Oproeren; Geschichte 1965-1992.; Samfundsvidenskab -- Sociologi; Electronic books; Electronic books